Mendelian randomization analysis of modifiable risk factors for breast cancer - Diabate Ousmane; Jie Liu; Ziyu Liu; Zongjiang Zhou; Liu Liu; Junpu Wang (Discover Oncology)
Abstract This review explores the role of Mendelian randomization (MR) in the analysis of modifiable risk factors for breast cancer. Breast cancer is the most common cancer in women, with risk factors including lifestyle, genetic predisposition, and hormonal influences. Mendelian randomization (MR) is a robust epidemiological tool, uses genetic variants to assess causal relationships between exposures and breast cancer risk. Evidence suggests that obesity, particularly in adulthood, is associated with elevated risk, while early obesity may be protective. Alcohol consumption shows a complex relationship, with adverse effects associated with problematic drinking behaviors rather than moderate drinking. Physical activity is associated with reduced breast cancer risk, likely through hormonal and metabolic pathways. Dietary factors, such as higher intake of monounsaturated fatty acids and vitamin E, appear protective, highlighting the importance of dietary choices. Methodological considerations, including pleiotropy and sample size, are crucial to ensure the validity of MR studies. Overall, this synthesis of existing studies demonstrates the importance of Mendelian randomization (MR) in identifying causal links between modifiable risk factors and breast cancer, which is essential for developing targeted prevention strategies.